Lactoferrin and Lysozyme Inhibit the Proteolytic Activity and Cytopathic Effect of Naegleria fowleri Enzymes - Moises Martinez-Castillo; Gerardo Ramírez-Rico; Mineko Shibayama; Mireya de la Garza; Jesús Serrano-Luna (Pathogens, 2024)
Naegleria fowleri is a ubiquitous free-living amoeba that causes primary amoebic meningoencephalitis. As a part of the innate immune response at the mucosal level, the proteins lactoferrin (Lf) and lysozyme (Lz) are secreted and eliminate various microorganisms. We demonstrate that N. fowleri survives the individual and combined effects of bovine milk Lf (bLf) and chicken egg Lz (cLz). Moreover, amoebic proliferation was not altered, even at 24 h of co-incubation with each protein. Trophozoites’ ultrastructure was evaluated using transmission electron microscopy, and these proteins did not significantly alter their organelles and cytoplasmic membranes. Protease analysis using gelatin-zymograms showed that secreted proteases of N. fowleri were differentially modulated by bLf and cLz at 3, 6, 12, and 24 h. The bLf and cLz combination resulted in the inhibition of N. fowleri-secreted proteases. Additionally, the use of protease inhibitors on bLf-zymograms demonstrated that secreted cysteine proteases participate in the degradation of bLf. Nevertheless, the co-incubation of trophozoites with bLf and/or cLz reduced the cytopathic effect on the MDCK cell line. Our study suggests that bLf and cLz, alone or together, inhibited secreted proteases and reduced the cytopathic effect produced by N. fowleri; however, they do not affect the viability and proliferation of the trophozoites.